Project Report On Fall Detection and Alert System For Elderly People - NILIMA PATHAK,SAHANA B V and SHRAVANTHI P V. (2013)
INTERNAL GUIDE : MEERA K S. EXTERNAL GUIDE:HARESH DAGALE. USN NO : 1MJ10EC057,1MJ10EC-83,1MJ10EC090. CARRIED OUT AT : Department Of Electonic System Engineering Bangalore-12 ACC N : PR2135
Keywords: Fall Detection and Alert System For Elderly People